Increased subventricular zone-derived cortical neurogenesis after ischemic lesion - Kreuzberg, Maria Mechthild; Kanov, Evgeny; Timofeev, Oleg; Schwaninger, Markus; Monyer, Hannah; Khodosevich, Konstantin (Experimental neurology, 2010)
In adult rodents stroke enhances neurogenesis resulting in the addition of neurons to forebrain regions such as striatum or cortex where postnatal neurogenesis under normal conditions plays a negligible role. In the cortex, new neurons are generated either from local cortical precursors that are activated by stroke or from precursors residing in the subventricular zone (SVZ) of lateral ventricles that under normal conditions supply neuroblasts by and large only for the olfactory bulb. In this study we used 5HT3A-EGFP transgenic mice in which all neuroblasts originating in the SVZ are EGFP-labeled. We induced stroke in these mice and by combination of EGFP detection with BrdU injections we labeled all post-stroke-generated SVZ-derived neuroblasts. We showed an increase in SVZ-derived neuroblasts 14 and 35days after stroke in the ipsilateral hemisphere. Post-stroke-generated SVZ-derived neuroblasts migrated to the cortex and survived for at least 35days representing 2% of BrdU-positive cells in peri-infarct area where they differentiate into mature neurons. Thus, stroke enhances SVZ neurogenesis and attracts newborn neurons to the injury zone.